The sisters are alright : changing the broken narrative of black women in America - Winfrey Harris, Tamara (Berrett-Koehler Publishers, 2015)
"Everyone seems to have an opinion about American black women--they need to get married, change their hair, act like 'ladies, ' and so on. Celebrated writer Tamara Winfrey Harris writes a searing account of being a black woman in America and explains why it's time for black women to speak for themselves"--Provided by publisher